Cervical Cancer Campaign: Correlation Between HPV Vaccine and Cervical Cancer Knowledge with HPV Vaccination Rate - Mariani Santosa; Ashley Karin Anjaya; Veronica Dwi Jani Juliawati; Robi Irawan; Yuliana (School of Medicine and Health Sciences, Atma Jaya Catholic University of Indonesia, 2023)
Introduction: Cervical cancer ranks second for the highest cancer cases in Indonesia. The main cause is recurring HPV infection. HPV infection commonly occurs when transmission by skin-to-skin contact or skin to mucosa contact is enough to spread it. One prevention effort is HPV vaccination, but there are still obstacles such as a lack of education and expensive prices. Methods: This study is an analytic cross-sectional study. Data was collected from February through March of 2023 gathering a total of 121 respondents. Questionnaires are used for data collection with 10 questions concerning cervical cancer and 11 questions regarding HPV vaccine knowledge. The Fisher exact probability test was used as bivariate analysis. Results: This study shows that students of the Faculty of Medicine and Health Sciences at Atma Jaya Catholic University of Indonesia have great knowledge regarding cervical cancer, adequate and great knowledge concerning the HPV vaccine with the majority reporting not being vaccinated (69,4%). Bivariate analysis shows no significant correlation between cervical cancer and HPV vaccine knowledge with HPV vaccination rate (p = 0,499 and p = 0,808). Conclusions: There is no significant correlation between cervical cancer and HPV vaccine knowledge with HPV vaccination rate among preclinical students of Faculty of Medicine and Health Sciences at Atma Jaya Catholic University of Indonesia.